The political economy of the third way: the relationship between globalisation and national economic policy - Lee, Simon (Edward Elgar Publishing, 2019)
The past 30 years are often depicted as an era of globalisation, and even more so with the recent rise of global giants such as Google and Amazon. This updated and revised edition of The Handbook of Globalisation offers novel insights into the rapid changes our world is facing, and how best we can handle them. With multi-disciplinary contributions from leading experts, this Handbook covers a broad spectrum of issues and opportunities surrounding modern globalisation. It explores the idea that globalisation is not new, natural or inevitable, but rather that current global arrangements are the result of corporate pressure and the choices of politicians. It highlights the fact that the deregulated, free market form of globalisation is not unavoidable and explores a new era of global co-operation based around a Green New Deal. It also considers the future of globalisation in the face of the Trump presidency, Brexit and the move towards more state-centred policies. This Handbook continues to be a vital resource for scholars, students and researchers of economics, international relations, and business and management who wish to gain a more in-depth understanding of globalisation from a variety of different disciplines. Politicians and policy makers will also benefit from the advice offered to avoid some of the increasingly negative impacts of our globalising world.
Keywords: Political economy; Third Way; Tony Blair; Globalisation; Economic policy